2005
DOI: 10.1097/01.inf.0000164765.12808.26
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Screening

Abstract: Challenges to implementation of group B streptococcal screening and prophylaxis include insufficient screening, suboptimal intrapartum antibiotics, disease despite negative screening cultures and timely communication of screening results at delivery. An awareness of such problems may lead to supplemental measures to further reduce group B streptococcal disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Risk of bias is higher in these studies because participants in the two arms are not contemporaneous, so other differences between these periods may contribute. The few observational studies that compare screening with concurrent controls often retrospectively compare women who have a culture result to all other women8990; this may be biased due to the risk of misclassification and because people who accept screening are systematically different from those who do not 8091. Finally, as most studies only assess early onset GBS infection confirmed on culture, changes in disease incidence may actually reflect a decreased likelihood of culturing GBS in the laboratory, owing to the presence of antibiotics in neonates’ blood 92.…”
Section: Uncertain Evidence On Screening Effectivenessmentioning
confidence: 99%
“…Risk of bias is higher in these studies because participants in the two arms are not contemporaneous, so other differences between these periods may contribute. The few observational studies that compare screening with concurrent controls often retrospectively compare women who have a culture result to all other women8990; this may be biased due to the risk of misclassification and because people who accept screening are systematically different from those who do not 8091. Finally, as most studies only assess early onset GBS infection confirmed on culture, changes in disease incidence may actually reflect a decreased likelihood of culturing GBS in the laboratory, owing to the presence of antibiotics in neonates’ blood 92.…”
Section: Uncertain Evidence On Screening Effectivenessmentioning
confidence: 99%
“…5 This striking and encouraging increase in screening rates was coupled with the elimination of previously reported racial and regional differences in screening. Screening for GBS was associated significantly with the use of other recommended prenatal screening tests and greater prenatal care utilization.…”
Section: Discussionmentioning
confidence: 86%
“…However, the study population was similar to that reported previously, allowing comparisons over time. 3,5 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations